Language, youth and identity in the 21st century : linguistic practices across urban spaces - Nortier, Jacomine; Svendsen, Bente A. (Cambridge : Cambridge University Press, 2015)
The language of young people is central in sociolinguistic research, as it is seen to be innovative and a primary source of knowledge about linguistic change and the role of language. This volume brings together a team of leading scholars to explore and compare linguistic practices of young people in multilingual urban spaces, with analyses ranging from grammar to ideology. It includes fascinating examples from cities in Europe, Africa, Canada and the US to demonstrate how young people express their identities through language, for example in hip-hop lyrics and new social media. This is the first book to cover the topic from a globally diverse perspective, and it investigates how linguistic practices across different communities intersect with age, ethnicity, gender and class. In doing so it shows commonalities and differences in how young people experience, act and relate to the contemporary social, cultural and linguistic complexity of the twenty-first century.
Language Practice and Positioning in Interaction: 10. Stylized voices of ethnicity and social division Lian Malai Madsen and Bente A. Svendsen; 11. Verbal teasing among young people in Kge and Eski ;ehir Hlya zcan, Lian Malai Madsen, lknur Keik and Jens Normann Jrgensen; Part VI. Language Practice and Urban Space: 12. Indexing locality: contemporary urban vernaculars in Belgium and Norway Finn Aars'ther, Stefania Marzo, Ingvild Nistov and Evy Ceuleers; 13. Urban youth speech styles in Kenya and the Netherlands Margreet Dorleijn, Maarten Mous and Jacomine Nortier; 14. Sociolinguistic practice among multilingual youth: comparing Swedish cities with Toronto Sally Boyd, James A. Walker and Michol F. Hoffman.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Language and languages -- Study and teaching (Higher) -- Social aspects; Second language acquisition -- History -- 21st century; Youth -- History -- 21st century; Public spaces -- History -- 21st century; Identity (Psychology) -- History -- 21st century; Multicultural education -- History -- 21st century; Sociolinguistics